Controlled Sulfurization Process for the Synthesis of Large Area MoS2 Films and MoS2/WS2 Heterostructures. Issue 4 (16th December 2015) - Chiappe, Daniele; Asselberghs, Inge; Sutar, Surajit; Iacovo, Serena; Afanas'ev, Valeri; Stesmans, Andre; Balaji, Yashwanth; Peters, Lisanne; Heyne, Markus; Mannarino, Manuel; Vandervorst, Wilfried; Sayan, Safak; et al.
Abstract : Large area MoS2 films with tunable physical‐chemical properties are grown on dielectric substrates by annealing of ultrathin Mo layers in the presence of a sulfur‐containing gaseous precursor. Different growth conditions are found to have a significant impact on material properties, including chemical composition, roughness, and grain sizes, thus shedding light on critical parameters that govern sulfurization processes for the synthesis of large area 2D transition metal dichalcogenides. Optimized growth conditions in combination with the use of single crystal sapphire substrates with atomically flat interface result in the formation of oriented MoS2 films with improved quality and electrical performance. On the basis of this versatile synthesis technique, an original double‐step process is presented for the synthesis of WS2 /MoS2 vertical heterostructures. Good uniformity of layers over large area has enabled first isolation of defects by electron spin resonance spectroscopy with densities correlated with mobility degradation and the first experimental characterization of the band alignment at the interfaces of MoS2, WS2, and their vertical stacks with the underlying SiO2 insulator. Abstract : Large area MoS2 films are grown on dielectric substrates by annealing of ultrathin Mo layers in the presence of a sulfur‐containing gaseous precursor. An original double‐step process is presented for the synthesis of WS2 /​MoS2 vertical heterostructures. Good uniformity of layers over a large area has enabled first isolation of defects by electron spin resonance spectroscopy with densities correlated with mobility degradation.